Conservative approach in adult right-sided Bochdalek hernia with an intrathoracic ectopic kidney - Husam El Sharu; Zaid Alwarawrah; Mohammad Alqaisieh; Ahmed Hebishy (Open Exploration Publishing Inc., 2023)
Bochdalek hernia (BH) is a congenital diaphragmatic defect primarily diagnosed in neonates and is usually left-sided. Adult diagnosis, especially of right-sided BH is exceedingly rare and usually presents with symptoms. Till now, only 31 cases have been diagnosed to be right-sided BH along with intrathoracic kidney. This report presents a 26-year-old asymptomatic male who was incidentally diagnosed with a massive right congenital diaphragmatic hernia. Imaging revealed severe abdominal herniation, a right intrathoracic ectopic kidney, and a right liver lobe hypoplasty along with hypertrophied left liver lobe extending down to the pelvic cavity. Several surgeons were consulted, with controversial opinions on whether elective surgery should be performed or withheld. Due to the high risk associated with surgery and the patient's choice, the surgery was deferred. For almost 18 months, the patient did not report any symptoms or complications. This case highlights the rarity of asymptomatic right-sided BH in adults and the challenges in determining a management approach. Also, it proposes a conservative approach for such patients as a management modality. Most extensive diagrammatic defect reported is estimated to have a neck defect of 10 cm. Most BH cases have been treated surgically and reports on the outcome of a conservative approach are exceedingly rare. In such cases, patient preferences and a thorough risk assessment play vital roles in decision-making regarding conservative versus surgical approaches.